Peningkatan Motivasi Belajar Siswa Pada Materi Sholat Jenazah dengan Metode Demonstrasi di Kelas 2 SMK Nawa Bhakti Kebumen - Anjani Rizkiana; Muhammad Fazar Setiadi; Siti Fatimah; Fuad Hasyim (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to determine the increase in student motivation in the material for the funeral prayer using the demonstration method in grade 2 at SMK Nawa Bhakti Kebumen. The research subjects were grade 2 students of SMK Nawa Bhakti Kebumen, totaling 33 students. The method used in this research is classroom action research. Data was collected using observation sheets and interviews. Data analysis was performed using a qualitative descriptive technique. The results of the analysis in cycle I showed that as many as 89% of students got a complete score in the ability to understand the quiet material for the funeral prayer. Whereas in cycle II as many as 99% of students obtained a complete score in the ability to demonstrate the funeral prayer. The results of the study show that the application of the demonstration method can increase student motivation in the material for the funeral prayer. Therefore, it is suggested that the demonstration method is more widely applied in learning in schools so as to increase student learning motivation and overall learning quality.